Coaching course ‘Become Who You Are’- The Impact on Students of Music Management in the Czech Republic - Omelkova, Kristyna (My University, 2020)
This study aims to find out about the career choices of students of Music Management and the impact of a career coaching course ‘Become Who You Are’ on the participants. Martin Soppe created the course and introduced it at universities in the Czech Republic. The course is using coaching methods and helps students in their career decision-making process. At the same time, it focuses on self-esteem, which is one of the main factors for successful professional and personal life. Content analysis was used for analysing the qualitative data. It provides flexibility in the research design and transfers valid results into context. The data analyses showed that the majority of the participants found the coaching course ‘Become Who You Are’ helpful. It helped them to clarify their future career paths as well as obtain new information. However, they did not consider the course as a life-changing experience. Furthermore, all the participants agreed that a similar career caching course should be part of a school curriculum. Therefore, scholars should consider including professional support for students’ aspirations and their career decision-making process.
Keywords: Career decision-making process, Career coaching, Self- efficacy, Self-concept, Art and Creativity, Motivation and transfer